2021
DOI: 10.1039/d1sc03048e
|View full text |Cite
|
Sign up to set email alerts
|

DsbA is a redox-switchable mechanical chaperone

Abstract: DsbA is a ubiquitous bacterial oxidoreductase that associates with substrates during and after translocation, yet its involvement in protein folding and translocation remains an open question. Here we demonstrate a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 66 publications
(87 reference statements)
0
11
0
Order By: Relevance
“…2c ). Remarkably, in the presence of 60 µM oxidized DsbA, a known force-dependent foldase chaperone 24 , the mechanical stability of talin increased to 14.3 ± 0.5 pN (Fig. 2d ).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…2c ). Remarkably, in the presence of 60 µM oxidized DsbA, a known force-dependent foldase chaperone 24 , the mechanical stability of talin increased to 14.3 ± 0.5 pN (Fig. 2d ).…”
Section: Resultsmentioning
confidence: 92%
“…By contrast, tunnel-associated chaperones possess the ability to increase the mechanical stability of their substrates. Such as oxidoreductase DsbA, a well-known model mechanical foldase, has the ability to increase the folding rate and mechanical stability of R3 24 , 77 , 78 . Hence, our results demonstrate that chaperones could modulate the mechanical stability of the FA protein talin, which is characterized by the change in the unfolding free energy barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The periplasmic oxidoreductase enzyme DsbA has a well-characterized function to transfer the disulfide bond to substrate proteins by reducing its catalytic CXXC motif and helps in the folding of cysteine-containing proteins. Interestingly, few studies revealed the role of DsbA in transporting cysteine-free proteins through translocon pores, suggesting its plausible chaperone activity independent of oxidoreductase activity. Therefore, we explore the mechanical chaperone activity of DsbA by using our substrate protein L, a cysteine-free globular protein. Unlike DnaJ or SecB, the refolding kinetics is greatly increased in the presence of DsbA, while a slight change was observed in unfolding kinetics (Figure D,E).…”
Section: Resultsmentioning
confidence: 99%
“…6). Since protein folding at the edge of any translocon pore act as a source of force generation (10,19), these chaperones might influence the translocation of the substrates (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%